Immunomodulation of MSCs and MSC-Derived Extracellular Vesicles in Osteoarthritis - Zhao, Xige; Zhao, Yanhong; Sun, Xun; Xing, Yi; Wang, Xing; Yang, Qiang (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoarthritis (OA) has gradually been recognized as a low-grade inflammatory state. Inflammatory infiltration of synovium by macrophages, T cells, B cells and other immune cells are often exhibited in OA patient, which play a key role in the pathogenesis of OA. Hence, orchestrating the local inflammatory microenvironment and tissue regeneration microenvironment is important to the treatment of OA. MSCs offer the advantages of cartilage regeneration due to their effective immunomodulatory properties and anti-inflammatory abilities. The paracrine eﬀect mediated by exosomes of MSCs, has been suggested for their curative eﬀect in recent years. In this review, we summarize the interactions and mechanism of MSCs or MSC-derived exosomes with OA-related immune cells and how this relates to the therapeutic effects of osteoarthritis. Additionally, we discuss the potential of MSC-exosomes as novel cell-free therapy for the clinical treatment of OA.